Survey of hereditary angioedema episodes and quality of life impairment through a patient-participatory registry - Morioke, Satoshi; Aikyo, Tatsuki; Tanaka, Akio; Matsubara, Daiki; Saito, Ryo; Iwamoto, Kazumasa; Yamasaki, Chisato; Kogetsu, Atsushi; Hamakawa, Nao; Isono, Moeko; Yamamoto, Beverley Anne; Matsumura, Yasushi; et al. (Journal of Cutaneous Immunology and Allergy, 2024)
Hereditary angioedema (HAE) adversely affects patients' social and daily life significantly, and the disease burden is high. We recruited study participants from a patient-participatory registry, Rare and Undiagnosed Diseases Study (RUDY) Japan, to better understand the broader effect of HAE on patients’ lives. Thirteen patients with HAE who registered between January 2019 and March 2021 completed an online questionnaire to record details of episodes and the angioedema quality of life (AE-QoL) questionnaire, in which they described the degree to which QoL was impaired. In all, 58 episodes were recorded, and self-reported data were accumulated from 24 returned AE-QoL questionnaires. The episodes peaked between approximately 06:00 and 07:00 hours and between approximately 16:00 and 20:00 hours. Of the 58 episodes, 38 (65.5%) were treated; 24 (63.2%) were treated at patients’ homes. The drugs used in treatment were hospital-administered human C1-inhibitor preparations for 14 episodes and home-administered icatibant for 26 episodes. Time between episode onset and treatment initiation and between episode onset and full recovery tended to be shorter with icatibant treatment at home. The total AE-QoL score was 37.1 ± 22.9, indicating great impairment of QoL, with particularly high scores in the fatigue/mood and fears/shame domains. Most previous studies of real-world HAE episodes have been retrospective, based on patients' memories. Collaboration between patients and researchers revealed the location of episodes, the time of day they appeared, treatments for episodes, and the degree to which patients’ QoL was impaired by HAE in this prospective study.